Continuous Testing Improvement Model - Mascheroni, Maximiliano Agustín (2021)
Continuous Delivery is a practice where high-quality software is built in a way that it can be released into production at any time. However, systematic literature reviews and surveys performed as part of this Doctoral Research report that both the literature and the industry are still facing problems related to testing using practices like Continuous Delivery or Continuous Deployment. Thus, we propose Continuous Testing Improvement Model (CTIM) as a solution to the testing problems in continuous software development environments. It brings together proposals and approaches from different authors which are presented as good practices grouped by type of tests and divided into four levels. These levels indicate an improvement hierarchy and an evolutionary path in the implementation of Continuous Testing. Also, an application called EvalCTIM was developed to support the appraisal of a testing process using the proposed model. Finally, to validate the model, an action-research methodology was employed through an interpretive theoretical evaluation followed by case studies conducted in real software development projects. After several improvements made as part of the validation outcomes, the results demonstrate that the model can be used as a solution for implementing Continuous Testing gradually at companies using Continuous Deployment or Continuous Delivery and measuring its progress.